O EFEITO DO SISTEMA DE CIMENTAÇÃO ADESIVA E TEMPO DE ARMAZENAMENTO NOS VALORES DE RESISTÊNCIA DE UNIÃO, NANODUREZA E MÓDULO DE ELASTICIDADE NO AMBIENTE INTRA-RADICULAR - Higashi, Cristian (2012)
The aim of this study was to assess the push-out bond strength, nanohardness and Young’s modulus of three resin cements used for luting fiber post. The measurements were taken at cervical (CT), middle (MT) and apical (AT) radicular thirds, at immediate time and after one year of storage in water. Root canals of 57 human teeth were endodontically treated and prepared to cementation of fiber post (White Post DC - FGM) using the cementation systems: Multilink [MUL] (Ivoclar Vivadent), Variolink II + Excite DSC [VAR] (Ivoclar Vivadent) and R RelyXTM Unicem [UNC] (3M ESPE). For the push-out test (n=16), after 24hs of water storage at 37ºC, half the sample (n=8) was transversely sectioned into 6 slices, being 2 slices for each radicular third, which were assess d at 0,5 mm/min. The remaining half (N=8) was kept unsectioned in deionized water at 37ºC for 1 year, followed by sectioning and measuring. For the nanoindentation test, the cemented samples (n=3) were stored in water at 37ºC for 24hs and after were longitudinally sectioned to perform the initial measurements of hardness and elastic’s modulus from cervical to apex. These same samples were stored in deionized water at 37ºC for 1 year and reassessed. The data were analyzed by three-way ANOVA and Tukey’s test (α=0.05). The mean and standard deviation of MUL bond strength (MPa) in AT (19.9 ± 3.9) was higher than MT (15.1 ± 4.7) and CT (14.9 ± 4.2) (p=0.00007). The immediate bond strength of AT (22.0 ± 4.9) decreased significantly after 1 year of water storage (15.1 ±4.1) (p=0.006). The MUL cement obtained higher values of Young’s modulus (GPa) in CT (9.2 ± 1.9) when compared to MT (6.6 ± 2.0) e AT (5.4 ± 2.6)(p=0.01). The AT has the lowest values of hardness (GPa) (0.40 ± 0.10) when compared to MT (0.45 ± 0.12) and CT (0.48 ± 0.11) (p=0.000001). The initial hardness of UNC cement (0.43 ± 0.12) decreased after 1 year of storage in water (0.35 ± 0.14) (p=0.0051). It was concluded that: 1) The bond strength of MUL cement was higher in AT, 2) The AT of the cements suffered higher bond degradation after 1 year of storage water, 3) The Young’s modulus of MUL cement was higher in CT, 4) The AT of all cements had lowest hardness values, 5) After 1 year of storage in water, the UNC cement had a significant decreased of hardness values.